An introduction to lean work design. - Fredendall, Lawrence D., (Supply and operations management collection., 2016)
Lean Work Design comes directly from our view that lean operations results from the work design. This book uses three existing work design theories to study lean operations and to identify the principles of lean operations. First, systems theory is used to conceptualize how lean operations differ from other work designs. Second, buffer theory, which views lean as a set of buffers to protect throughput from variance, is used to more effectively manage buffers. Third, organizational information processing theory is used to understand how the lean work design processes different types of information. So, lean work design is a work design that maximizes system productivity and effectiveness while minimizing the system's buffer costs. Lean does this by achieving tighter integration of its system components by using work design methods that incorporate a systems view of the organization. Appropriate work design methods consciously seek to incorporate a systems view and coordination into the design of a production or service process. This book is not about the many tools in lean. Rather, it focuses on understanding the lean concepts and how to actively use these concepts to create structure and facilitate communication. The book introduces the fundamentals of Lean operations that are a key to creating a Lean Work Design. It provides a knowledge structure that can be adapted to the day- to-day problems encountered by managers of many different types of work systems.